Teachers’ Performance and Students’ Achievement in Araling Panlipunan - Lobendino, Rhoanne; Garcia, Genevive (Studies in Technology and Education, 2025)
Araling Panlipunan (AP) represents a critical facet of the Philippine educational landscape, fostering the development of students' socio-cultural awareness and civic engagement in basic education. This study analyzed the complex relationship that exists between teacher instructional effectiveness and student’s academic achievements in AP within the domain in a specific subset of Junior High School both public and private at Legislative District II in the Province of Isabela, Philippines. The study employed methodological framework based on descriptive-correlational paradigms to organize an empirical investigation through organized questionnaires that are given to groups of teachers, students, and school heads/principals. Analysis of Variance (ANOVA), T-Test, and Pearson Correlation Coefficient are used as statistical techniques that provide a foundation for methodical data analysis that reveal differences and subtle relationships and patterns in the dataset. The results revealed a demographic makeup that is typified by a high proportion of female, and experienced teachers who have a strong preference for AP specialization. Evaluations of teacher’s performance from themselves and school heads/principals demonstrated continuously high performance, with consistency found in age and gender across demographic groups. AP student performance is of a high caliber, and there are statistically significant correlations that indicate the relationship between particular teaching strategies and improved exam scores. These results provide teachers with useful information that emphasizes how important effective teaching strategies are for promoting academic success in the AP subject.